Bioethics for clinicians: 28. Protestant bioethics - Pauls, Merril (2002)
“PROTESTANT” IS A TERM APPLIED TO MANY DIFFERENT Christian denominations, with a wide range of beliefs, who trace their common origin to the Reformation of the 16th century. Protestant ideas have profoundly influenced modern bioethics, and most Protestants would see mainstream bioethics as compatible with their personal beliefs. This makes it difficult to define a uniquely Protestant approach to bioethics. In this article we provide an overview of common Protestant beliefs and highlight concepts that have emerged from Protestant denominations that are particularly relevant to bioethics. These include the sovereignty of God, the value of autonomy and the idea of medicine as a calling as well as a profession. Most Canadian physicians will find that they share certain values and beliefs with the majority of their Protestant patients. Physicians should be particularly sensitive to their Protestant patients' beliefs when dealing with end-of-life issues, concerns about consent and refusal of care, and beginning-of-life issues such as abortion, genetic testing and the use of assisted reproductive technologies. Physicians should also recognize that members of certain Protestant groups and denominations may have unique wishes concerning treatment. Understanding how to elicit these wishes and respond appropriately will allow physicians to enhance patient care and minimize conflict.